ANALISIS FAKTOR YANG MEMPENGARUHI BIAYA PENYELENGGARAAN IBADAH HAJI DI INDONESIA - Mochammad Arif Budiman (Jurnal Hukum Islam, 2016)
The cost for pilgrimage (BPIH) has always changed over the years following the economic circumstances. This research attempts to analyze two external factors, i.e. oil price and exchange rate which are predicted to influence the BPIH in Indonesia. Using vector autoregressive (VAR), it is found that oil price has related with BPIH while exchange rate, relying on annual exchange rate data, has no relation with BPIH. Further, based on variance decomposition function, the contribution of oil price and exchange rate to BPIH is around 9.8% and 6.93% respectvely. This finding suggests that both factors do not give major influences on the rate of BPIH in Indonesia.rcumstances. This research attempts to analyze two externalfactors, i.e. oil price and exchange rate which are predicted to influence theBPIH in Indonesia. Using vector autoregressive (VAR), it is found that oil pricehas related with BPIH while exchange rate, relying on annual exchange ratedata, has no relation with BPIH. Further, based on variance decompositionfunction, the contribution of oil price and exchange rate to BPIH is around9.8% and 6.93% respectvely. This finding suggests that both factors do notgive major influences on the rate of BPIH in Indonesia.